2021
DOI: 10.5194/cp-2021-18
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maastrichtian-Rupelian paleoclimates in the southwest Pacific – a critical evaluation of biomarker paleothermometry and dinoflagellate cyst paleoecology at Ocean Drilling Program Site 1172

Abstract: Abstract. Sea surface temperature (SST) reconstructions based on isoprenoid glycerol dialkyl glycerol tetraether (isoGDGT) distributions from the Eocene southwest (sw) Pacific Ocean are unequivocally warmer than can be reconciled with state-of-the-art fully coupled climate models. However, the SST signal preserved in sedimentary archives can be affected by contributions of additional isoGDGT sources. Methods now exist to identify and possibly correct for overprinting effects on the isoGDGT distribution in mari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 119 publications
(303 reference statements)
7
19
0
Order By: Relevance
“…Foraminiferal assemblages in the Taylor White succession confirm that this transgression progresses through the Waipawa Formation and into overlying Wanstead Formation (Naeher et al, 2019). A similar geological history is inferred for the Tasmanian margin where a major runoff event is linked to Waipawa deposition (Hill and Exon, 2004;Bijl et al, 2021). Therefore, the only plausible 575 explanation for a rapid influx of terrestrial plant matter is one or more eustatic falls in sea level, eroding coastal vegetation and flushing the debris into offshore basins.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Foraminiferal assemblages in the Taylor White succession confirm that this transgression progresses through the Waipawa Formation and into overlying Wanstead Formation (Naeher et al, 2019). A similar geological history is inferred for the Tasmanian margin where a major runoff event is linked to Waipawa deposition (Hill and Exon, 2004;Bijl et al, 2021). Therefore, the only plausible 575 explanation for a rapid influx of terrestrial plant matter is one or more eustatic falls in sea level, eroding coastal vegetation and flushing the debris into offshore basins.…”
supporting
confidence: 60%
“…We interpret this to indicate that Waipawa organofacies is the result of a rapid influx of terrestrial OM into the marine environment. Corroborating evidence for a marked increase in terrestrial runoff at this time has recently been reported in a 480 study of biomarkers and dinoflagellate paleoecology from ODP Site 1172 (Bijl et al 2021). The foraminiferal data (Naeher et al, 2019) suggest that this runoff event occurred while basins were progressively deepening, which is consistent with long-term passive-margin subsidence throughout New Zealand (King et al, 1999).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Dredging exercise confirms the continental origin of the of the plateau (Exon et al, 1997). However, the age of the guyot/seamount (dated as 36 Ma; Lanyon et al, 1993) disqualifies the ETP itself as the potential source of the terrestrial organic matter (Bijl et al, 2021).…”
Section: Tectonic Evolution and Depositional Settingmentioning
confidence: 82%
“…The proximity of our study site to the Tasmanian Gateway places it in an excellent geographical position to identify potential climate or tectonic impacts on terrestrial vegetation of the Australo-Antarctica region. To further investigate potential links between the terrestrial and marine realm we also and mean annual air temperature (MAATsoil) reconstruction from the same site (Bijl et al, 2021). Our study reveals a significant terrestrial cooling ~3 Ma prior to the EOT, and a warming in the earliest Oligocene which is most likely controlled by transient rebound of atmospheric pCO2 and sustained deepening of the Tasmanian Gateway.…”
Section: Introductionmentioning
confidence: 91%